Analysis of Entropy Generation Minimization in Circular Porous Fins. (22nd October 2012) - Saedodin, Seyfolah; Sadeghi, Siamak; Shahbabaei, Majid
Abstract : This work introduces a simple method of exergy analysis in a typical circular porous fin. The entropy generation of any thermodynamic system provides a useful measure of the extent of irreversibility. The irreversibility causes the loss of useful work (exergy) in the system and hence the loss of exergy has to be minimized. Entropy generation is a parameter that quantifies the loss of exergy. Circular fins are relatively good heat transfer augmentation features with superior aerodynamic performance and as a result find application in some solar air heaters. In this paper, the entropy generation in a circular porous fin is calculated and its performance is compared with respect to entropy generation. Also shown in porous fins, with increase of porosity. The entropy generation number N s will increase; also states with porosity have higher entropy generation number than N s states with nonporosity (φ = 0 ). Also at higher Reynolds number the effect of the Re L on N s T is negligible, but at lower Reynolds number the variation of the N s P is negligible. Also we can see that with increased porosity (φ ), the entropy generation (S g e n ) will decrease. The entropy generation is calculated for circular porous fins with mass constraint.